2021
DOI: 10.3390/ijerph18126643
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Psychosocial Variables, Availability of Physical Activity Resources in Neighborhood Environment, and Out-of-School Physical Activity among Chinese Adolescents

Abstract: This study aimed to evaluate the relationship between psychosocial variables (peer support, parental support, autonomous motivation, and controlled motivation), availability of physical activity resources in a neighborhood environment, and out-of-school moderate to vigorous physical activity (MVPA) among Chinese adolescents. The questionnaire of Family Life, Activity, Sun, Health, and Eating (FLASHE) Study was used to collect information on demographics, socioeconomic status, psychosocial variables, available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Low SES families are more concerned about the safety of their neighbors and have fewer physical activity resources available ( Estabrooks et al, 2003 ). However, high SES families are more likely to be a convenient play spaces, good sports equipment, and the easy availability of transportation to sports, and more likely to receive encouragement and support from peers ( Qiu et al, 2021 ). Furthermore, families with higher family wealth can provide more sufficient funds for their children on weekends and even set an example for their children to participate in sports ( Mo et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low SES families are more concerned about the safety of their neighbors and have fewer physical activity resources available ( Estabrooks et al, 2003 ). However, high SES families are more likely to be a convenient play spaces, good sports equipment, and the easy availability of transportation to sports, and more likely to receive encouragement and support from peers ( Qiu et al, 2021 ). Furthermore, families with higher family wealth can provide more sufficient funds for their children on weekends and even set an example for their children to participate in sports ( Mo et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that the difference of fathers’ education level may be related to their different attitudes and expectations toward their children’s participation in PA ( Schuz et al, 2017 ). The possible reason for the gender difference is that boys may highly enjoy participating in physical activities and games ( Seabra et al, 2013a ) and perceive themselves as more physically competent than girls ( Qiu et al, 2021 ). Furthermore, fathers may be more restrictive for vigorous PA in girls than in boys due to cultural conservations ( Gustafson and Rhodes, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The home environment (i.e., the availability of PA resources) was also correlated with autonomous motivation, suggesting that the home environment may influence autonomous motivation for MVPA. A previous study demonstrated that high school girls did not engage in out-of-school MVPA in the neighborhood environment [ 45 ]. Thus, the home environment might be especially poignant for girls.…”
Section: Discussionmentioning
confidence: 99%
“…One’s environment can influence personal food intake [ 14 ]. Parents play a critical role for the physical and psychosocial environment of their children [ 15 , 16 ]. Parents can affect their children’s eating patterns through their attitudes, behaviors, and feeding styles [ 17 ].…”
Section: Introductionmentioning
confidence: 99%